Využitie OCT‐angiografie (OCT‐A) pri sclerosis multiplex - Skirková, Miriama; Moravská, Monika; Horňák, Marek; Szilasi, Jozef; Szilasiová, Jarmila (Neurologie pro praxi, 2023)
Optical coherence tomography angiography (OCT-A) is a novel, non-invasive, fast, repeatable, 3D imaging method for retinal, choroidal, and optic nerve vessels. OCT-A has the potential to become a new biomarker of various ophthalmological (e.g. glaucoma, diabetic retinopathy, age-related macular degeneration) and neurological disorders. Retinal microcirculation share similar features with cerebral small blood vessels, thus OCT-A may be considered a "window" for the detection of microvascular changes which are associated with neurodegenerative disorders, such as multiple sclerosis. In this review, we summarize recent findings regarding the utility of OCT-A as a novel, prospective biomarker for early diagnosis and monitoring of multiple sclerosis.
Keywords: dospělí; neurodegenerativní nemoci; Humans; klinická studie jako téma; Neurodegenerative Diseases; Microvascular Density; oči; lidé středního věku; Middle Aged; mikrovaskulární denzita; nervus opticus; optická koherentní tomografie; oční symptomy; retina; Adult; Tomography, Optical Coherence; Eye Manifestations; roztroušená skleróza; Multiple Sclerosis; ženské pohlaví; Female; lidé; Optic Nerve; Eye; Retina; Clinical Studies as Topic